2023
DOI: 10.5114/jcb.2023.127051
|View full text |Cite
|
Sign up to set email alerts
|

Complication and response assessment of high-dose-rate endorectal brachytherapy boost in neo-adjuvant chemoradiotherapy of locally advanced rectal cancer with long-term outcomes

Abstract: Purpose: To identify efficacy, complication, and pathologic response of high-dose-rate endorectal brachytherapy (HDR-BRT) boost in neo-adjuvant chemoradiotherapy (nCRT) of locally advanced rectal cancer.Material and methods: Forty-four patients who met eligibility criteria were included in this non-randomized comparative study. Control group was recruited retrospectively. nCRT (50.40 Gy/28 fr. plus capecitabine 825 mg/m 2 twice daily) was administered to both groups before surgery. In the case group, HDR-BRT (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“… 42 For operable LARC patients, using HDR‐ICBT as a boost to the EBRT dose to achieve a better response rate is a widely used approach. Previous studies have shown that dose escalation with HDR‐ICBT results in higher complete response rates 10 , 12 , 14 , 15 and improved downstaging, 10 , 11 with no significant increase in toxicity or surgical complications 9 , 10 , 12 , 14 compared to neoadjuvant CRT alone, and that most of the adverse effects could be controlled medically (Table 2 ). 10 , 11 The T downstaging may be closely associated with improved sphincter retention, 10 , 16 , 17 which would significantly improve patients' quality of life.…”
Section: Clinical Application Of Hdrebt In Rectal Cancermentioning
confidence: 97%
See 1 more Smart Citation
“… 42 For operable LARC patients, using HDR‐ICBT as a boost to the EBRT dose to achieve a better response rate is a widely used approach. Previous studies have shown that dose escalation with HDR‐ICBT results in higher complete response rates 10 , 12 , 14 , 15 and improved downstaging, 10 , 11 with no significant increase in toxicity or surgical complications 9 , 10 , 12 , 14 compared to neoadjuvant CRT alone, and that most of the adverse effects could be controlled medically (Table 2 ). 10 , 11 The T downstaging may be closely associated with improved sphincter retention, 10 , 16 , 17 which would significantly improve patients' quality of life.…”
Section: Clinical Application Of Hdrebt In Rectal Cancermentioning
confidence: 97%
“… 7 Subsequent studies have reported its advantages in achieving pCR as a neoadjuvant monotherapy in the early stage 8 or as a boost to EBRT in locally advanced rectal cancer (LARC). 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 HDREBT is now widely applied across various stages of rectal cancer and has shown promising results in achieving high complete response rates. HDREBT also has the potential to enable nonoperative management and improve organ preservation rates in selected cases.…”
Section: Introductionmentioning
confidence: 99%